Sliding Window Algorithm for Evaluation of Medical Symbols - Ikromov Shakhobiddin Shamsutdinovich; Akbarov Chingiz Adkhamjanovich; Juraev Gulomjon Primovich (Researchparks Publishing, 2022)
This article discusses about sliding window algorithm for evaluation of medical symbols and given some important information.